Efficacy and safety of treatment with dupilumab for severe asthma: A systematic review of the EAACI guidelines—Recommendations on the use of biologicals in severe asthma. Issue 5 (1st April 2020) - Agache, Ioana; Song, Yang; Rocha, Claudio; Beltran, Jessica; Posso, Margarita; Steiner, Corinna; Alonso‐Coello, Pablo; Akdis, Cezmi; Akdis, Mubeccel; Canonica, Giorgio Walter; Casale, Thomas; Chivato, Tomas; et al.
Abstract: Dupilumab, a fully human monoclonal antibody against interleukin‐4 receptor α, is approved as add‐on maintenance treatment for inadequately controlled type 2 severe asthma. This systematic review evaluated the efficacy, safety and economic impact of dupilumab compared to standard of care for uncontrolled severe asthma. PubMed, EMBASE and Cochrane Library were searched for RCTs and health economic evaluations. Critical and important asthma‐related outcomes were evaluated. The risk of bias and the certainty of the evidence were assessed using GRADE. Three RCTs including 2735 subjects >12 years old and 24‐52 weeks of follow‐up were included. Dupilumab reduced with high certainty severe asthma exacerbations (Incidence rate ratio 0.51; 95% CI 0.45‐0.59) and the percentage use of oral corticosteroid use (mean difference (MD) −28.2 mg/d; 95% CI −40.7 to −15.7). Asthma control (ACQ‐5), quality of life (AQLQ) and rescue medication use [puffs/d] improved, without reaching the minimal important clinical difference: ACQ‐5 MD −0.28 (95% CI −0.39 to −0.17); AQLQ MD +0.28 (95% CI 0.20‐0.37); and rescue medication MD −0.35 (95% CI −0.73 to +0.02). FEV1 increased (MD +0.15; 95% CI +0.11 to +0.18) (moderate certainty). There was an increased rate of dupilumab‐related adverse events (AEs) (moderate certainty) and of drug‐related serious AEs (low certainty). The incremental cost‐effectiveness ratio of dupilumab versus standard therapy was 464 000$/QALY (moderate certainty). More data on long‐term safety are needed both for children and for adults, together with more efficacy data in the paediatric population.